RANCANG BANGUN E-COMMERCE PADA TOKO MADU SPORT - Ricky Rahmadian Rahmadian (FKOM UNIKU, 2016)
Toko Madu Sport is a sporting goods store, ranging from clothing, shoes, and so on. Currently sales are limited only in the City of Kuningan alone, due to the absence of communication media between Madu Sport Shop with consumers from outside kota.Berdasarkan background has been described, research this will design an e-commerce system, this system will show all the supply of various types of products offered complete with product specifications and prices. So that sellers and buyers can access the availability of products and can transact online anytime and anywhere. Therefore, it will be designed and built e-commerce system in sports honey shop that is able to provide information about the product and can order an online product so that consumers can access and order products in sports honey shop whenever and wherever. From the research that has been done by the authors that by building e-commerce informarsi system in web-based honeycomb shop can facilitate the store management in managing sales data due to have a database terintegerasi with the internet and has been computerized well, and certainly very easy for consumers in look at items sold in sports honey shop without having to go to the store because the data items, stock items and purchases of goods can be done online.